Beet root as potential ingredient for functional foods development - Fuertes, Sonia Paula (2014)
The objective of this work was to develop cereal bars with beetroot (Beta vulgaris L var. conditiva) as a functional ingredient. Beet bars were obtained mixing dried ingredients (whole oat, corn crips and grated beet) and sugar matrix (glucose and honey), then the mix was spread in an aluminum plate, moulded and baked. Control bars (without beet) were obtained with the same procedure. Water activity, moisture content, color and texture of the formulated snack bars were analyzed. Active compounds of beetroot and bars samples, betalains and polyphenols, were also determined. Beet bars showed lower values of water activity (0.35) than those obtained for the control bars (0.41), indicating good microbiological stability of the formulated product. Moisture content values of 9.2 % for beet bars were obtained, similar to those found in control samples (7.7 %). Beet bars showed lower L and higher a* values compared to control bars, due to the redness of beetroot. Similar b* values were obtained for both, control and beet bars, denoting yellowness in the color of samples. Texture profile analysis and a three-point bending test were applied to the snack bars. Fracture stress, elastic modulus and fracture energy values were higher for the beet bars compared to the control, showing that beet incorporation modified the texture of the bars. With regard to the active compounds, high contents of betalains (> 95 %) were retained in the beet bars after baking. Beetroot addition increased the polyphenol content of the final product compared to the control, improving its nutritional profile. Beet bars had a good acceptance level (68 %) when were evaluated by an unentrained sensorial panel, showing that this product could be consumed as a healthy snack.